POMOLOGICAL TRAITS OF FIG (Ficus carica L.) GENOTYPES COLLECTED IN THE WEST MEDITERRANEAN REGION IN TURKEY - Sadiye Gozlekci (Journal of Animal and Plant Sciences, 2011)
Fig (Ficus carica L.) is one of the most important fresh and dried fruits for both consumers and food industry throughout world and is produced in a limited number of countries. As a leader producer in the world, Turkey has important fig genetic resources as well. However in most parts of the country, in particular coastal regions, local fig genotypes are continuously subjected to genetic erosion and therefore, it is necessary to determine, collect, describe and also to maintain them in situ and ex situ. This study we aimed to evaluate local fig germplasm in Alanya and Kemer districts in Mediterranean region of Turkey. The results showed that the investigated pomological traits of fig genotypes displayed significant differences within both districts. Fig samples collected from Alanya are more suitable for making marmalade and jam because they had relatively small fruits, while figs sampled from Kemer are generally considered good as fresh consumption due to their relatively big fruit size. These valuable fig genetic resources are under in-situ conservation to use in future breeding programmes.
Keywords: Fig; Ficus carica; pomological traits; diversity.